IF YOU HAD YOUR BIRTHDAY PARTY ON THE MOON - Lapin, Joyce (Union Square Kids, 2019)
What is so great about having your birthday party on the moon? For starters, you can ride in a rocket with your friends and eat cake upside down. You and your friends can bounce and glide in a low-gravity playground. And since one Moon day equals 30 Earth days, your celebration will last a whole month! Filled with facts about the moon and space, this out-of-this-world adventure is perfect for sharing at home and school.